2015
DOI: 10.1099/jmm.0.000058
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of genes related to biofilm formation in multidrug-resistant Acinetobacter baumannii isolated from clinical settings

Abstract: Acinetobacter baumannii is a Gram-negative bacteria associated with hospital-acquired infections. Definitely, antimicrobial resistance and biofilm formation capabilities of clinical isolates have threading potential to persistence in the hospital environment and colonization on medical equipment. Twenty-seven multidrug-resistant clinical isolates were selected from a collection of A. baumannii samples isolated from clinical settings. PCR assays showed the frequencies of genes related to biofilm formation: ompA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
4
21
1
2
Order By: Relevance
“…Overall the AbOmpA is a conserved protein, but there are minor amino acids variations in four extracellular loops of beta-barrel domain of this protein (data have not been published). In our previous study the presence and expression of AbOmpA protein were confirmed in all MDR A. baumannii clinical isolates (Badmasti et al, 2015b). In this study data showed the ratio of IgG1/IgG2c in AbOmpA vaccination was 0.95.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Overall the AbOmpA is a conserved protein, but there are minor amino acids variations in four extracellular loops of beta-barrel domain of this protein (data have not been published). In our previous study the presence and expression of AbOmpA protein were confirmed in all MDR A. baumannii clinical isolates (Badmasti et al, 2015b). In this study data showed the ratio of IgG1/IgG2c in AbOmpA vaccination was 0.95.…”
Section: Discussionsupporting
confidence: 64%
“…For the Bap factor we used one conserved immunodominant region from four regions based on Rahbar et al study (Rahbar et al, 2010). Our previous study revealed the frequency of Bap factor in MDR A. baumannii clinical isolates is 30% (Badmasti et al, 2015b). Al though this factor has low frequency but for covering all pathogenic isolates and satisfied protection we added it in combination vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistics of National Institutes of Health and the Center for Disease and Prevention, 65-80% human infections were caused by biofilm-forming bacteria [58]. Based on the multi-functional characteristics of biofilm formation, a series of genes associated with bacterial adhesion and biofilm formation were identified, such as AbOmpA, beta-lactamase PER-1 (blaPER-1) and biofilm-associated protein (Bap) [59]. Indeed, the OmpA of A. baumannii ATCC19606 plays a dominant role in forming stable biofilm on plastic surface (Fig.…”
Section: Abompa Induces Biofilm Formationmentioning
confidence: 99%
“…Biofilm formation was quantified by the microtiter plate assay method as described previously (15). Briefly, A. baumannii species were grown overnight in trypticase soy broth (TSB) (Merck, Germany) with 0.25% glucose at 37°C.…”
Section: Biofilm Formationmentioning
confidence: 99%